EFEKTIFITAS KEGIATAN KELOMPOK SIMPAN PINJAM KHUSUS PEREMPUAN DI KECAMATAN KAUDITAN KABUPATEN MINAHASA UTARA - Gianina Amelinda Rantung; Lyndon R.J. Pangemanan; Charles R. Ngangi; Ellen G. Tangkere (Universitas Sam Ratulangi, 2014)
ABSTRACTThis research has been purposed to describe the effectiveness of Savings and Loans For Woman Group Activity (SPP) in Kauditan Subdistrict North of Minahasa Regency on 2012-2013. The benefit of this research is to provide information about the effectiveness of activity operated by saving and loans for woman group in Kauditan Subdistrict North of Minahasa Regency and to give an information to those who need that information.Data collected are primary data and secondary data. The primary data was obtained by distributing questionnaires to respondents and the secondary data was obtained from the institutions associated with this research. The sampling method was done by